2001
DOI: 10.1074/jbc.m106528200
|View full text |Cite
|
Sign up to set email alerts
|

The Enzymatic and DNA Binding Activity of PARP-1 Are Not Required for NF-κB Coactivator Function

Abstract: The mammalian poly(ADP-ribose) polymerase 1 (PARP-1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
262
5
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(288 citation statements)
references
References 61 publications
19
262
5
2
Order By: Relevance
“…Immunoblot analysis of the precipitates with anti-Myc revealed that, while full-length PARP-1 as well as mutants lacking either the active site or the DBD equally bound E2F-1 (Figure 6c, lanes 1-3, respectively), the mutant lacking the DBD-AD did not (Figure 6c, lane 4), indicating that the protein interaction site is located in the central AD. Consistently, this central AD of PARP-1 includes a BRCT domain that has been implicated in interactions with various other proteins, including XRCC1 (Masson et al, 1998), HPV18 E2 (Lee et al, 2002), and NF-kB p50 and p65 (Hassa et al, 2001). Binding of PARP-1 to E2F-1 and induction of E2F-1 promoter activity during S-phase reentry is therefore independent of the DNA binding or enzymatic activity of PARP-1, consistent with our results showing that PARP-1 neither binds internal sequences of the E2F-1 promoter nor modifies E2F-1 by poly(ADP-ribosyl)ation.…”
Section: Parp-1 Physically Associates With E2f-1 In Vitro As Revealedmentioning
confidence: 81%
See 1 more Smart Citation
“…Immunoblot analysis of the precipitates with anti-Myc revealed that, while full-length PARP-1 as well as mutants lacking either the active site or the DBD equally bound E2F-1 (Figure 6c, lanes 1-3, respectively), the mutant lacking the DBD-AD did not (Figure 6c, lane 4), indicating that the protein interaction site is located in the central AD. Consistently, this central AD of PARP-1 includes a BRCT domain that has been implicated in interactions with various other proteins, including XRCC1 (Masson et al, 1998), HPV18 E2 (Lee et al, 2002), and NF-kB p50 and p65 (Hassa et al, 2001). Binding of PARP-1 to E2F-1 and induction of E2F-1 promoter activity during S-phase reentry is therefore independent of the DNA binding or enzymatic activity of PARP-1, consistent with our results showing that PARP-1 neither binds internal sequences of the E2F-1 promoter nor modifies E2F-1 by poly(ADP-ribosyl)ation.…”
Section: Parp-1 Physically Associates With E2f-1 In Vitro As Revealedmentioning
confidence: 81%
“…To further map the interaction domains in PARP-1 and E2F-1, we performed protein-binding experiments using full-length PARP-1 as well as truncation mutants lacking the C-terminal catalytic active site, the DBD, or the DBD-AD of the protein. CMV-Myc tagged PARP-1 expression vectors with full-length PARP cDNA (PARP-fl) or truncation mutants (DBD-ADpartCAT(-p 1À829 ), AD-CAT(-p 338À1014 ), CAT(-p 525À1014 ); (Hassa et al, 2001)) were used to synthesize wild-type and mutant PARP-1 by in vitro transcription and translation. Immunoblot analysis of the products with antibodies to the c-Myc epitope confirmed the presence of 120-, 94-, 74-, and 54-kDa immunoreactive proteins corresponding to full-length PARP-1 and truncated products lacking the catalytic active site, DBD, or DBD-AD of PARP-1 (lanes 1-4, respectively) (Figure 6b).…”
Section: Parp-1 Physically Associates With E2f-1 In Vitro As Revealedmentioning
confidence: 99%
“…106,107 Subsequent in vitro studies have then shown that PARP-1 interacts with both p65 and p50 by two independent domains. [108][109][110] However, there are contradictory data concerning the importance of the PARP-1 enzymatic activity for NF-kB activation. 108,109,[111][112][113] TNF is able to activate PARP-1 via the production of ROS, which in turn causes PARP-inducing DNA damage.…”
Section: Ask1mentioning
confidence: 99%
“…[108][109][110] However, there are contradictory data concerning the importance of the PARP-1 enzymatic activity for NF-kB activation. 108,109,[111][112][113] TNF is able to activate PARP-1 via the production of ROS, which in turn causes PARP-inducing DNA damage. However, it is an open question whether TNF-induced PARP-1 activation via ROS is a prerequisite for its role in TNF-induced NF-kB activation or whether PARP-1 exerts its NF-kB-supporting capability independent of prior activation.…”
Section: Ask1mentioning
confidence: 99%
“…Both GCC and ATA promoter types responded to the drug, although the latter type responded more at lower concentration of the inhibitor. Conversely, when PARP-1 was overexpressed by cotransfection with a PARP-1-expression vector, 58 both the GCC and ATA promoters' activities were inhibited dose dependently (Figure 5b). This inhibition was not seen with an enzymatically inactive mutant of PARP-1 (with a point mutation, E988K, in the catalytic domain) 59 on the GCC promoter whereas the mutant PARP-1 enhanced the ATA promoter activity.…”
Section: Apoptotic Cells Induce Il-10 Production In Macrophagesmentioning
confidence: 99%